Diagnostic Challenges in Extrapulmonary Tuberculosis: A Single-Center Experience in a High-Resource Setting at a German Tertiary Care Center - Jonas Wilmink; Richard Vollenberg; Ioana D. Olaru; Julia Fischer; Jonel Trebicka; Phil-Robin Tepasse (Infectious Disease Reports, 2025)
Background/Objectives: Extrapulmonary tuberculosis accounts for a significant portion of tuberculosis cases, presenting unique diagnostic challenges due to its heterogeneous manifestations and paucibacillary nature. This study aims to fill this gap by evaluating the diagnostic outcomes and correlations between different specimen types and test results. Methods: A retrospective analysis of electronic medical records of patients diagnosed with TB between January 2013 and December 2023 was carried out. The data extracted included patient demographics, comorbidities, TB classification, specimen types, microbiological test results, and time intervals to diagnosis. Statistical analysis was applied to compare the variables between pulmonary and extrapulmonary/disseminated TB groups. Results: Most patients were male (62.4%) and born outside of Germany (74.2%). Comorbidities, such as diabetes, cardiac disease, immunosuppressed status, and HIV, were common. Among the 194 patients, 98 had pulmonary TB, and 96 had extrapulmonary/disseminated TB. A comparison of pulmonary vs. extrapulmonary TB showed that extrapulmonary TB patients had a longer diagnostic delay (p = 0.013), more symptoms (p = 0.001), and more complications (42.7% vs. 16.3%, p < 0.001). Diagnostic challenges were evident, with multiple invasive procedures required in 43.5% of the extrapulmonary TB cases. Conclusions: This study highlights the complex clinical presentation of tuberculosis, particularly in patients with extrapulmonary and disseminated forms, who experience delayed diagnosis and more complications. These challenges in diagnosing extrapulmonary TB emphasize the need for improved diagnostic strategies and early identification, especially in high-risk populations.